Improvement of the drying property of lumbang oil III low temperature crystalization - Arida V.P.; Lubi, E.V.; Fumar, Q.C.; Serrano, D. (1980)
The mixed fatty acids (or their methyl esters) derived from lumbang were fractionated into groups by crystallization from solvents (acetone/petroleum ether) at low temperature. The experimentally obtained fractions had iodine values which were close to those of the corresponding pure fatty acids or their esters, indicating that the method effected a fairly neat separation of the mixed fatty acids or their esters. The best ratio was 1: 4 (fatty acid to petroleum ether or methyl ester to acetone); best crystallization time was at 60 minutes.
Includes bibliographical references (page 71)
Keywords: Chemistry; Lumbang oil -- Drying properties; Drying improvement; Low temperature crystallization